2017
DOI: 10.1016/j.jinteco.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two tails: Productivity distribution and the gains from trade

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 44 publications
4
23
0
Order By: Relevance
“…The rankings are statistically significant typically at well beyond a 1 percent level. Our results are consistent with the evidence provided by Combes et al (2012) and Nigai (2017) using French data. The data strongly suggest that Pareto provides a poor fit, and that lognormal is a reasonable distribution for TFP.…”
Section: Manufacturing Tfpsupporting
confidence: 94%
See 1 more Smart Citation
“…The rankings are statistically significant typically at well beyond a 1 percent level. Our results are consistent with the evidence provided by Combes et al (2012) and Nigai (2017) using French data. The data strongly suggest that Pareto provides a poor fit, and that lognormal is a reasonable distribution for TFP.…”
Section: Manufacturing Tfpsupporting
confidence: 94%
“…Sager and Timoshenko (2017) show that a convolution of lognormal and Pareto fits best using Brazilian export sales data. Nigai (2017) shows that a mixture of lognormal and Pareto fits the firm productivity distribution of French firms the best and that its adoption affects the estimation of the gains from trade. Armenter and Koren (2015) finds that the Pareto shape parameter required to match the exporter size premium (how much larger the average exporter is) would be about 1.65, and thus it is difficult to reconcile models of selection into exporting by firm size with a size distribution generated by realistic Pareto parameterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Upon making certain parametric assumptions about the functional form of the wage distribution, the Gini coefficient and the average wage are sufficient statistics to impute wages for all percentiles of the distribution per country and year. In particular, this is possible when assuming that wages follow either (i) a log-normal, (ii) a Pareto, (iii) or a mixture of the two distributions, where the upper tail is Pareto and the rest is log-normally distributed (see Nigai 2017). We provide details on this mixture and describe the imputation and calibration procedures for wage percentiles in the Appendix.…”
Section: Globalization and Relative Labor Income Tax Burdens Acrosmentioning
confidence: 99%
“…11 Calibrated to the U.S. data, Melitz and Redding (2015) set the Pareto shape parameter for firm productivity to be 4.25, and Bernard, Redding and Schott (2009) set it equal to 4. Estimating using French firm level data, Nigai (2017) found that a Pareto shape parameter would take a value of 1.9. Lower values of k correspond to greater firm heterogeneity.…”
Section: The Seller's Problemmentioning
confidence: 99%